The future of sensory substitution, addition, and expansion via haptic devices - Eagleman, David M.; Perrotta, Michael V. (Frontiers in Human Neuroscience, 2023)
Haptic devices use the sense of touch to transmit information to the nervous system. As an example, a sound-to-touch device processes auditory information and sends it to the brain via patterns of vibration on the skin for people who have lost hearing. We here summarize the current directions of such research and draw upon examples in industry and academia. Such devices can be used for sensory substitution (replacing a lost sense, such as hearing or vision), sensory expansion (widening an existing sensory experience, such as detecting electromagnetic radiation outside the visible light spectrum), and sensory addition (providing a novel sense, such as magnetoreception). We review the relevant literature, the current status, and possible directions for the future of sensory manipulation using non-invasive haptic devices.